Pemetaan Distribusi Sumber Air di Jalur Pendakian Gunung Tandikek via Nagari Singgalang - Fernado, Gito Jandio; Prarikeslan, Widya (Lembaga Yasin AlSys, 2024)
This research was carried out on Mount Tandikek with the aim of mapping the distribution of water sources along the Mount Tandikek climbing route via the Singgalang village and determining the quality of the water. The method used is the spring coordinate plotting method, for water quality using quality standards PERMENKES no. 492 of 2010. The results of the research found 4 springs along the route. Spring 1is at the start of the climb, spring 2 is located near shelter 3, spring 3 is not far from spring 2, and spring 4 is around the peak of Mount Tandikek. Water quality is based on the parameters tested, water color parameters 1, 2, and 3 are suitable, while spring 4 is not suitable. The odor parameters of springs 1, 2, and 3 are suitable, while spring 4 is no suitable. The turbidity parameters are suitable for all spring sources. The taste parameters of springs 1, 2, and 3 are suitable, while spring 4 is not suitable. The pH parameters of springs 1, 2, and 3 are suitablem while spring 4 is not suitable. And sulfate parameters for all springs.